2013
DOI: 10.1080/15536548.2013.10845689
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Investigation of Privacy Awareness and Concerns on Social Networking Sites

Abstract: Privacy affects every user who exchanges information over the Internet. In the past few years, the growth of information on social networks (such as Facebook, Twitter, Linkedln) has increased exponentially. Companies are harvesting this information with and without the knowledge ofindividuals. While the exchange ofinformation and seamless interaction between individuals and groups has become an easy task, issues related to this exchange, such as information privacy and security, have created new challenges. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 43 publications
3
8
0
1
Order By: Relevance
“…It shows older users have greater concerns about their privacy. This finding supports Hazari and Brown's (2013) argument that privacy concern increases with age. Our study results indicate that females are more concerned about their information privacy, which supports the position of Nowak and Phelps (1992) but contradicts Hazari and Brown (2013), who stated that gender difference is not a significant factor in determining users' levels of privacy concern.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…It shows older users have greater concerns about their privacy. This finding supports Hazari and Brown's (2013) argument that privacy concern increases with age. Our study results indicate that females are more concerned about their information privacy, which supports the position of Nowak and Phelps (1992) but contradicts Hazari and Brown (2013), who stated that gender difference is not a significant factor in determining users' levels of privacy concern.…”
Section: Discussionsupporting
confidence: 87%
“…The survey Consumer action "Do not track" (2013) results showed that 87% of their participants strongly agreed that they have the right to make choices regarding their information privacy and want more control. According to Hazari & Brown (2013), the employed users of social networks websites are more likely to control their privacy preferences than the unemployed users because it can have a negative influence on their employment status and relationships. Young and Quan-Haase (2009) found that students made some effort to control their personal information in their profiles to protect themselves.…”
Section: Privacy Concernsmentioning
confidence: 99%
See 1 more Smart Citation
“…The default setting for a Twitter account is that all tweets are public-that is, they can be read by anyone with or without a Twitter account (Hazari & Brown, 2013). A user may change the account settings to be protected, which means that he must approve each person who wants to subscribe to (i.e., read) his or her tweets.…”
Section: Mechanics Of Twittermentioning
confidence: 99%
“…Sheehan (2002) found that users' education and age correlate with their level of concern about online privacy. Hazari and Brown (2013) studied whether demographic variables can affect Internet users' privacy concerns and, thus, their attitudes toward using social networking sites. In contrast to the results from Sheehan and from Regan, Fitzgerald, and Balint, their research found that age was not correlated with online privacy concerns.…”
Section: Introductionmentioning
confidence: 99%